2019
DOI: 10.1016/j.radonc.2019.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Validation of T2- and diffusion-weighted magnetic resonance imaging for mapping intra-prostatic tumour prior to focal boost dose-escalation using intensity-modulated radiotherapy (IMRT)

Abstract: Highlights5 mm mapping prostate biopsies correlated with imaged intra-prostatic tumour.Diffusion-restricted tumour of ≥0.5 cm3 can be dose-escalated with confidence.Tumours of <0.5 cm3 should not be dose-escalated.Diffusion-weighted MR has good diagnostic accuracy for dominant tumour lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The accuracy of mp-MRI against a template biopsy gold standard has been reported in a subset of these patients. 18 All patients commenced hormone therapy after the mp-MRI. ADT was prescribed in accordance with local guidelines, giving short or long course ADT with initial bicalutamide for prevention of testosterone flare.…”
Section: Protocol Interventionmentioning
confidence: 99%
“…The accuracy of mp-MRI against a template biopsy gold standard has been reported in a subset of these patients. 18 All patients commenced hormone therapy after the mp-MRI. ADT was prescribed in accordance with local guidelines, giving short or long course ADT with initial bicalutamide for prevention of testosterone flare.…”
Section: Protocol Interventionmentioning
confidence: 99%
“…(2) While the dose delivered to the prostate is typically homogenous in external RT compared to brachytherapy, recent studies have shown that dose escalation to the dominant intraprostatic lesion (DIL), detected via multi-parametric MRI (mp-MRI) scans (3,4), could increase the tumor control probability (TCP). (5,6) Such dose escalation has been shown to be feasible with brachytherapy (3,(7)(8)(9)(10)(11)(12) and photon X-ray beams using volumetric modulated arc therapy (VMAT), (4,8,(13)(14)(15) Tomotherapy, (16) particle therapy, (9,17) and Cyberknife. (18) Proton therapy provides superior dose distributions and dosimetric advantages over photon X-ray beams in many sites.…”
Section: Introductionmentioning
confidence: 99%
“…2,5,26 Therefore, segmentation of suspicious MRI lesions as an alternative strategy is meaningful and is needed in clinical practice, based on the clinically acceptable correlation between the two kinds of lesions. [26][27][28] This study first paid attention to the deep learning-based segmentation of suspicious MRI lesions, contributing to the clinical practice of boosting these lesions during radiation delivery. An MRI database with manual contours was created from our clinical data for this objective.…”
Section: Introductionmentioning
confidence: 99%
“…Under the assumption that the visible MRI lesion is at higher risk of local failure than the other part of the prostate gland, some groups have looked at intraprostatic lesion boosts by dose‐escalation to the MRI visible lesion 2,5,26 . Therefore, segmentation of suspicious MRI lesions as an alternative strategy is meaningful and is needed in clinical practice, based on the clinically acceptable correlation between the two kinds of lesions 26–28 …”
Section: Introductionmentioning
confidence: 99%